Motivación del Personal de la Unidad de Hemodiálisis “DIAL-RÍOS” Ventanas - Galecio Cevallos, Mildred Minoska (2020)
In the "DIA-RIOS" Ventanas hemodialysis unit, the staff is not motivated to correctly carry out their activities, which is affecting this institution to carry out the achievement of its objectives. In other words, when employees do not receive the cancellation of their salary on time, they choose not to carry out their work efficiently, which creates an unpleasant environment for their colleagues, since documentation and cleaning and care of patients and machinery, in addition many of these employees choose to apply to another company, which generates one more inconvenience, such as the recruitment of personnel, for which the person trained for this area must be selected and if not the same employees They must impart their knowledge, to this is added the lack of the necessary hardware and equipment to carry out daily activities. In the opposite case, if all these factors exist positively within a company, the employees will be motivated to carry out their work and thus provide good care to both patients and their families, and they will enjoy an environment pleasant to carry out different teamwork and thus achieve the scope of both personal and institutional benefits.